Engineering Design and Rapid Prototyping - Kamrani, Ali K.; Nasr, Emad Abouel (Springer US : Imprint: Springer, 2010)
"Engineering Design and Rapid Prototyping" offers insight into the methods and techniques that allow for easily implementing engineering designs by incorporating advanced methodologies and technologies. This book contains advanced topics such as feature-based design and process planning, modularity and rapid manufacturing, along with a collection of the latest methods and technologies currently being utilized in the field. The volume also: -Provides systematic design and solution methodologies for both design and manufacturing -Discusses product life cycle development and analysis for ease of manufacture and assembly -Offers applied methods and technologies in rapid prototyping and manufacturing "Engineering Design and Rapid Prototyping" will be extremely valuable for any engineers and researchers and students working in engineering design.